SEKULERISASI DAN NEOLIBERALISME MELALUI HARMONISASI STANDAR AKUNTANSI INTERNASIONAL : IFRS - Sulistyowati, Wiwit Apit (PERMANA, 2010)
Globalization such as other trade activities between countries and the emergence of multinational companies, resulting in the need for an accounting standard is widely accepted around the world. Comparable accounting standards is required by multinational companies, and also by the users of financial statements to evaluate the performance of companies on a global scale and to help making decisions relating to the securities. IFRS serve as the main reference the financial accounting standards development in Indonesia because IFRS is a very robust standard. Preparation is supported by the international advisory board of experts and from around the world. With already declared on IFRS convergence program, then in 2012 all the standards issued by the Financial Accounting Standards Board IAI will refer to IFRS and applied by the entities. Adoption of accounting and the current educational system has been separated from the reality of Indonesian society, because education systems and accounting concepts taken directly from the West without the codification and significant adjustments. Accounting and accounting education system is basically bringing values